A Study on the need of entrepreneurship local content curriculum in Bandung Senior High School. (March 2019) - Susilana, R; Dewi, L; Ali, M
Abstract: This study discusses the needs of entrepreneurship local content curriculum in Senior High School (SHS) based on the assessment of potential local entrepreneurship resources and relevant competencies needed. There were 20 students and 20 teachers involved in the survey who were selected using purposive sampling method. The need assessment was administered in form of questionnaire and interview to explore the potential entrepreneurship resources and relevance competencies needed for each type of entrepreneurship. The data were further analyzed using percentage and cross tabulation (Chi-squares) statistical methods. There are common competencies needed for running each area of entrepreneurship such as marketing strategy, bookkeeping, financial management, and maximizing customer satisfaction. The above competencies are expected to meet United Nation's The 2030 Agenda for Sustainable Development, especially Goal 4 and Goal 8: (1) To ensure inclusive and equitable quality education and promote lifelong learning opportunities for all and; (2) Promote sustained, inclusive and sustainable economic growth, full and productive employment and decent work for all. The implication of this study is that every school is expected to arrange the scheduling program and provide competent teachers capable of implementing proper teaching and learning processes and mode of delivery system to facilitate the students acquiring competencies needed in entrepreneurship.